2004
DOI: 10.1002/cncr.20761
|View full text |Cite
|
Sign up to set email alerts
|

Solving the dilemma of the immunohistochemical and other methods used for scoring estrogen receptor and progesterone receptor in patients with invasive breast carcinoma

Abstract: BACKGROUNDThe authors attempted to resolve the dilemma posed by the lack of unanimity concerning the optimal immunohistochemical (IHC) method for determining and scoring estrogen receptor (ER) and progesterone receptor (PR).METHODSSections for IHC were prepared from paraffin embedded tumor samples from 402 patients with lymph node positive breast carcinoma who had biochemical receptor values (obtained with the dextran‐coated charcoal [DCC] method) and who were enrolled in a prospective, randomized trial (Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 29 publications
0
58
0
1
Order By: Relevance
“…Recently, a refined assessment of hormone receptors in breast carcinoma has become necessary to select therapeutic agents according to the recommendations and guidelines for postoperative adjuvant systemic therapy of early breast cancer proposed by the International Consensus Panel during the St Gallen Conference in 2005 (Goldhirsch et al, 2005). The guidelines proposed 3 disease responsiveness categories: endocrine responsive, endocrine response uncertain, and endocrine nonresponsiveAs to the method for the detection and quantification of estrogen receptor (ER) and progesterone receptor (PR), immunohistochemical methods have been preferred because of their relative simplicity, low cost, speed of performance, application to small samples, precise identification of reactive elements, simple methods of fixation and storage, ability to be applied to archival material (Fisher et al, 2005), and better ability to predict response to adjuvant endocrine therapy owing to validation studies for ER (Harvey et al, 1999) and PR (Mohsin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a refined assessment of hormone receptors in breast carcinoma has become necessary to select therapeutic agents according to the recommendations and guidelines for postoperative adjuvant systemic therapy of early breast cancer proposed by the International Consensus Panel during the St Gallen Conference in 2005 (Goldhirsch et al, 2005). The guidelines proposed 3 disease responsiveness categories: endocrine responsive, endocrine response uncertain, and endocrine nonresponsiveAs to the method for the detection and quantification of estrogen receptor (ER) and progesterone receptor (PR), immunohistochemical methods have been preferred because of their relative simplicity, low cost, speed of performance, application to small samples, precise identification of reactive elements, simple methods of fixation and storage, ability to be applied to archival material (Fisher et al, 2005), and better ability to predict response to adjuvant endocrine therapy owing to validation studies for ER (Harvey et al, 1999) and PR (Mohsin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective adjuvant studies conducted on archival tissue, one by Ferno et al [30] on 98 patients which received adjuvant tamoxifen, the other reported by Harvey et al [31]showed that estrogen receptor positivity determined by IHC significantly predicted improved disease free survival in patients receiving adjuvant tamoxifen therapy. To our knowledge only three other studies [17][18][19] used randomized clinical trial populations receiving adjuvant therapy but the cohort of patients were smaller, had shorter duration of follow up and mixed treatment arms [17,18]. Regan at al re-evaluated and reported results from International Breast Cancer Study Group (IBCSG) trial VIII (pre-and perimenopausal patients) and trial IX (postmenopausal patients).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry and cytosol assays were shown to yield similar predictive and prognostic information [15][16][17], but the majority of these studies had a short follow-up and many patients received a range of therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While ER and PR scores were assessed; only nuclear expression was concerned (Lester et al, 2009;Hammond et al, 2010) and for ER staining of >10% of tumor nuclei was considered positive. PR expression was considered to be positive if the nuclei of more than 1% of cells were stained positive (Diaz et al, 2004;Fisher et al, 2005). HER2 score assessment was made according to intensities and the proportions of the cells which showed membrane staining (Lester et al, 2009;Gutierrez and Schiff, 2011).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%